Effectiveness of infertility counseling on pregnancy rate in infertile patients undergoing assisted reproductive technologies: A systematic review and meta-analysis - Maleki-Saghooni, Nahid (Int J Reprod Biomed, 2017)
BACKGROUND: Psychological interventions such as counseling for infertile patients seem to increase pregnancy rate. OBJECTIVE: The aim of this systematic review and meta-analysis was to examine if counseling improves pregnancy rate among infertile patients. Thus, randomized controlled trials investigating the effect of counseling on pregnancy rate in infertile patients undergoing ART were pooled in a meta-analysis. MATERIALS AND METHODS: The databases of PubMed, Scopus, Cochrane, Google Scholar, and Persian databases including SID, Iran Medex, and Magiran were searched from 1997 to July 2016 to identify relevant articles. Included studies were trials on infertile patients (women or couples) receiving counseling independent of actual medical treatment. The outcome measure was pregnancy rate. Out of 620 relevant published trials, a total of nine RCTs were ultimately reviewed systematically and included in a meta-analysis to measure the efficacy of counseling on pregnancy rate. Odds ratio and Risk difference were calculated for pregnancy rate. All statistical analyses were done by Comprehensive Meta-analysis Version 2. RESULTS: Nine RCTs involving 1079 infertile women/couples were included in the study. The findings from RCTs indicated significant effect of counseling on pregnancy rate so that there was a positive impact of counseling on pregnancy rate (OR= 3.852; 95% CI: 2.492-5.956; p=0.00) and (RD= 0.282; 95%; CI: 0.208-0.355; p=0.00). CONCLUSION: Counseling was found to improve patients’ chances of becoming pregnant. So counseling represents an attractive treatment option, in particular, for infertile patients who are not receiving medical treatments.